2021
DOI: 10.1007/s00376-021-0215-y
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Method for Bias Correction of ECMWF 24–240 h Forecasts

Abstract: Correcting the forecast bias of numerical weather prediction models is important for severe weather warnings. The refined grid forecast requires direct correction on gridded forecast products, as opposed to correcting forecast data only at individual weather stations. In this study, a deep learning method called CU-net is proposed to correct the gridded forecasts of four weather variables from the European Centre for Medium-Range Weather Forecast Integrated Forecasting System global model (ECMWF-IFS): 2-m temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…It retains the convolution and pooling layers from CNN to extract the main features of the raw data, and adds skip connections, which can identify and retain features at different spatial scales. So far, U-net has been widely applied to the convection prediction, statistical downscaling and the model forecast postprocessing (Sha et al, 2020a(Sha et al, , 2020bDupuy et al, 2021;Han et al, 2021;Lagerquist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It retains the convolution and pooling layers from CNN to extract the main features of the raw data, and adds skip connections, which can identify and retain features at different spatial scales. So far, U-net has been widely applied to the convection prediction, statistical downscaling and the model forecast postprocessing (Sha et al, 2020a(Sha et al, , 2020bDupuy et al, 2021;Han et al, 2021;Lagerquist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this, an increasing number of studies are being performed that apply advanced DL models in the contexts of weather forecasting (McGovern et al, 2017), climate projection (Reichstein et al, 2019), and Earth system science (Schultz et al, 2021). Specifically, as discussed by Düben et al (2021), there are many potential applications of DL in each component of the workflow for NWP, such as data assimilation (e.g., Hatfield et al, 2021), physical parameterization (e.g., Han et al, 2020), statistical downscaling (e.g., Sha et al, 2020), and post-processing (e.g., Han et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al (2020) assessed various machine learning (ML) models for the bias correction of extreme air temperatures and found that ML-based models have greatly improved R 2 values and reduced bias. Han et al (2021) further applied a U-shaped NN (U-Net) with encode and decode layers into postprocessing for the 2-m temperature, 2-m relative humidity, 10-m wind speed, and 10-m wind direction and obtained remarkable improvements.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies showed that emerging machine learning techniques had been successfully and extensively applied in precipitation rate retrieval, increasingly becoming an important direction of precipitation estimation. Nevertheless, few studies used modern Deep Learning (DL) techniques [28], where multiple processing layers representing multiple levels of abstraction exist between the input and the output of a DL neural network (NN) [29][29] [30]. In addition, there is a key problem in the current deep learning algorithm for precipitation retrieval: Although the trained model may have high accuracy and beat previous benchmarks, they are only applied to some specific data sets.…”
Section: Introductionmentioning
confidence: 99%